Thrombotic microangiopathy in renal transplantation, tacrolimus as a causative agent - Rodriguez-Mori, Juan E. (2020)
Thrombotic microangiopathy (TMA) is an unusual complication associated to the use of tacrolimus in renal transplantation. This condition may be related to infections, antibody-mediated rejection (AMR), disease recurrence or de novo TMA, and toxicity of calcineurin inhibitors. Generally, this condition presents in non-complete forms, which makes diagnosis difficult, and irreversible lesions may supervene. This case features the presence of a viral infection, and data suggesting rejection with the concomitant tacrolimus use. Therapy includes plasmapheresis and the use of monoclonal antibodies such as eculizumab. Nonetheless, in this particular case suspending therapy or switching from tacrolimus to another agent were good cost-effective measures.